MARKETING MIX (4C) CREATES PURCHASING DECISIONS WITH IMPLICATIONS FOR LOYALTY IN SHOPEE PLATFORM USERS - Taufik Zulfikar; Afina Aprilia Riyajana; Didin Saepudin (SEAN Institute, 2023)
The revolution in information technology has enabled consumers to make purchasing decisions online. This leads to the argument that marketers should focus on consumer needs and preferences before deciding on product, pricing, channels, or promotion. To achieve this, manufacturers need to switch from the traditional 4P marketing mix to the 4C mix, which emphasizes customer solutions, convenience, cost, and communication. This study aimed to examine the influence of the 4C marketing mix on purchasing decisions and its implications for loyalty. The study used a quantitative method, collecting primary data through questionnaires distributed to 100 Shopee platform users in the city of Bandung. Path analysis was used to analyze the data. The results show that consumer, cost, and communication have a significant influence on purchasing decisions, while convenience does not. Furthermore, cost, convenience, and communication have an influence on loyalty, but consumer does not. Purchase decision acts as an intervening variable only in the indirect effect of consumers on loyalty through purchasing decisions, while for the indirect effect of cost, convenience, and communication on loyalty, purchase decisions are not intervening variables.